A gestão da segurança pública municipal no estado do Rio de Janeiro - (:unkn) unknown (Ministério Público do Estado da Bahia, 2008)
This article presents a diagnostic on the organization of municipal public safety institutions in the state of Rio de Janeiro. The administrative and organizational structures along with the principle aspects of the institutional procedures of the City Police are analyzed. It is argued that a database that stockpiles information on police work is essential for the management of public safety.
The administration of municipal public safety in the state of Rio de Janeiro
Keywords: Segurança pública; Gestão; Guardas Municipais; Vigilância patrimonial; Códigos de Posturas Municipais; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO